Diagnostic Analysis of mZN Microscopy and PCR for Detection of Cryptosporidiosis in Goat Kids – A Molecular Epidemiological Study - Atul Kumar Sharma; K. Gururaj; Anjana Goel; Rama Sharma; Souvik Paul; Dinesh Kumar Sharma (The Indian Veterinary Journal, 2024)
The occurrence of Cryptosporidium species infection and its risk factors in neonatal goats is less explored. Also it is due to the fact that diseases like colibacillosis and neonatal viral enteritis complex caused by Group A rotaviruses and Bovine corona viruses can co-exist with Cryptosporidium and can lead to mixed infections and the latter is often overlooked. Therefore, in the current research we explored the cryptosporidial occurrence in neonatal goats of Mathura district of Uttar Pradesh, India. In this study, a total of 644 faecal samples were collected from neonatal goats at different villages and certain organized farms of Mathura district age-wise, season-wise and breed-wise, and were examined for Cryptosporidium based on modified Ziehl-Neelsen technique, conventional 18SSU rRNA nested PCR assay. The overall prevalence of Cryptosporidium infection in goats based on microscopy was 36.80% (237/644; p value <0.0001) and 18SSU rRNA nested PCR 52.95% (341/644; p value <0.0001) respectively. Cryptosporidium species typing was also done using 18SSU rRNA nested PCR-RFLP product using enzymes Mbo-II, Ssp-I and Vsp-I, which revealed species including C. parvum C. bovis, C. ryanae, C. hominis and C. andersoni. Also the infection was clinically associated based on age, gender and seasons to identify the causal relationships that precipitate the cryptosporidial infection in goat kids. Since mZN microscopy based screening requires expertise and may sometimes be confuse with other weak acid fast bodies and also due to low sensitivity, combination of diagnostic tests are used in this study to identify the best test combination that yields best statistical fit in terms of kappa-agreement and McNemar’s test.